2010
DOI: 10.1093/annonc/mdp425
|View full text |Cite
|
Sign up to set email alerts
|

High dose intensity doxorubicin in aggressive non-Hodgkin's lymphoma: a literature-based meta-analysis

Abstract: High DI doxorubicin based should be considered in patients with aggressive NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Dosages regularly used in chemotherapeutic protocols for horses are extrapolated from other species, and cyclophosphamide dose optimization has not been reported in horses. Dose intensity refers to the dose of active drug over time, and multiple studies in humans and animals with cancer have shown that increasing chemotherapeutic dose intensity correlates with increased antitumor effect . Chemotherapeutic drug dose escalation is a strategy of gradual dose increases with careful monitoring for toxicity, utilized to determine the highest tolerated dose and thereby achieve higher dose intensity and maximum efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Dosages regularly used in chemotherapeutic protocols for horses are extrapolated from other species, and cyclophosphamide dose optimization has not been reported in horses. Dose intensity refers to the dose of active drug over time, and multiple studies in humans and animals with cancer have shown that increasing chemotherapeutic dose intensity correlates with increased antitumor effect . Chemotherapeutic drug dose escalation is a strategy of gradual dose increases with careful monitoring for toxicity, utilized to determine the highest tolerated dose and thereby achieve higher dose intensity and maximum efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgkin lymphomas are essentially curable with standard chemotherapy treatments of doxorubicin, bleomycin, vinblastin, and darcarbazine, but improvements can still be made in reducing off‐target side effects 233. Non‐Hodgkin lymphomas have historically been treated with standard chemotherapy of cyclophosphamide, doxorubicin, vincristine, and prednisone 234. Antibody based therapy with Rituximab has been shown to improve response in both first‐line treatments and in patients with relapsed or refractory cancers 235.…”
Section: Applications Of Targeted Therapiesmentioning
confidence: 99%
“…The outcome of this study determined that doxorubicin should be used for the treatment of aggressive non-Hodgkin's lymphomas and dose intensity of doxorubicin was a key factor in predicting patient survival. Further, a meta-analysis of published randomized controlled trials comparing chemotherapy regimens incorporating doxorubicin at a high dose with standard CHOP therapy was conducted and their conclusions were consistent with the Kwak and colleagues study [35]. Altogether, levels of TOP2A in BLs are elevated relative to immortalized B cells and that high dose doxorubicin in addition to standard CHOP therapy may improve Burkitt's lymphoma patient outcome through TOP2A mediated doxorubicin response.…”
Section: Discussionmentioning
confidence: 53%